Penetapan Kembali Desa Warunggahan sebagai Sima di Tuban Jawa Timur - Khabibah, Armyatul; Tara Wiguna, I Gst Ngurah (Humanis; Vol 24 No 1 (2020), 2020)
Inscriptions as textual media and material products of past human activities are included in the category of artifacts. Most of the inscriptions issued by ?r? Mah?r?ja Nar?rrya Sa?gramawijaya contained the stipulation of s?ma . Reestablishment of Waru?gahan village as a gift of s?ma by ?r? Mah?r?ja Nar?rrya Sa?gramawijaya is a form of retribution given by K?tanagara to P?duka Mpu?ku ?r? Buddhaketu for his services while accompanying K?tanagara to become king in Singhasari. The reestablishment of s?ma in Waru?gahan village gave privileges to residents of the s?ma region, one of which was tax deduction. The tax allocation that was supposed to be submitted to the kingdom was used to maintain the dharmma (sacred building) periodically and the cost of building maintenance funding could be guaranteed.